RAD Conference Proceedings 2017
DOI: 10.21175/radproc.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Behaviors and Catecholamine Content in Prefrontal Cortex and Hippocampus of Chronically Stressed Rats

Abstract: Abstract. Chronic stress induces over-activation and dysfunction of stress-activated systems, resulting in further brain damage and depressive-like behavior. Depression is a potentially life-threatening disorder that affects people and, therefore, it is one of the most important public health problems. This study examined the effects of chronic restraint stress (CRS: 2 hours × 14 days) on the anxiety-like and depression-like behaviors in rats, as well as on the possible changes in the concentrations of dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
(27 reference statements)
2
6
0
Order By: Relevance
“…It is known that an increase of monoamine neurotransmitter levels is an important therapeutic strategy for several neuropsychiatric disorders [39]. In the present study, we found that lithium treatment increased both protein levels of hippocampal TH and concentration of DA in chronically stressed rats to the levels found in unstressed animals [6, 7], which indicates that lithium enabled de novo synthesis of hippocampal DA in chronically stressed rats. Lithium may have induced the gene expression of hippocampal TH in stress condition through the activator protein-1 (AP-1) transcription factor pathway [40].…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…It is known that an increase of monoamine neurotransmitter levels is an important therapeutic strategy for several neuropsychiatric disorders [39]. In the present study, we found that lithium treatment increased both protein levels of hippocampal TH and concentration of DA in chronically stressed rats to the levels found in unstressed animals [6, 7], which indicates that lithium enabled de novo synthesis of hippocampal DA in chronically stressed rats. Lithium may have induced the gene expression of hippocampal TH in stress condition through the activator protein-1 (AP-1) transcription factor pathway [40].…”
Section: Discussionsupporting
confidence: 67%
“…Our results show that it is possible that lithium has an effect on normalizing neuroplasticity in chronically stressed rats. In addition, in our earlier studies, we found that CRS induced a significant decrease of hippocampal DA concentration [6]. Literature data have confirmed that the decreased concentration of DA was observed in many psychiatric and neurodegenerative disorders, for example, depressive illness and Parkinson's disease [19, 38].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations